The short story as a form of self-legitimation and self-reflexion (on the example of a Bosnian and Hercegovinian short story) - Softić-Gasal, Larisa (Anafora, 2022)
The short story, as a new literary genre of Bosnian and Herzegovinian literature of the transitional period, has found its way to enter the market of recipients. The role of the reader as a member of a specific cultural group is very important when trying to define the short story. The reader is one of the participants of a contextual network that makes all literary works “open”, thus offering enormous possibilities of detailed reading, rereading and reflection. Previous attempts to define the short story depict it as a modern, contemporary and intensive prose form and a response to the internal raptures of modern recipients. Engaging readers in the process of creating has been achieved by the well-known Brechtian waking up to reality which breaks, to some extent, both the narrative and theatrical illusions. By comparing the so called open forms of stories/dramas,a particular pattern of linguistic behaviour of characters is observed that reflects their difficulties to articulate their feelings, to express them and to reveal them to themselves and to others. Most of the compared short stories/dramas of open forms are characterized by impaired communication between characters. Their statements barely follow one another or, in turn, come with hesitation and have the characteristics of intellectual disability. Zlatko Topčić’s stories Garib and Hasanaginica present the social problem of accepting the allegorical morality/mentality of male society, while promoting the characters as carriers of both the burden of otherness and their own immanent perspective of resistance. Games of signifiers (God, ownership, state) represent the power of the ideology of modern class society. Many short stories from the period of transition of Bosnian and Herzegovinian society are a valuable challenge to the reader’s sensibility to grasp the relativity of the perspective of all socially assumed standards of evaluation.